2021
DOI: 10.1186/s12884-021-03830-5
|View full text |Cite
|
Sign up to set email alerts
|

Fetal weight estimation by automated three-dimensional limb volume model in late third trimester compared to two-dimensional model: a cross-sectional prospective observational study

Abstract: Background Accurate estimation of fetal weight is important for prenatal care and for detection of fetal growth abnormalities. Prediction of fetal weight entails the indirect measurement of fetal biometry by ultrasound that is then introduced into formulae to calculate the estimated fetal weight. The aim of our study was to evaluate the accuracy of fetal weight estimation of Chinese fetuses in the third trimester using an automated three-dimensional (3D) fractional limb volume model, and to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
7
1
1
Order By: Relevance
“…A multicenter study indicated that the inclusion of automated FLV measurements improved the proportion of correctly classified birthweight ± 10% in >80% of cases than 73.8% for the INTERGROWTH-21 st model 64 . For Chinese fetuses in the third trimester, particularly newborns weighing <3500 g, the percentage of estimated error ≤ 5% using the automated limb volume estimation software (58.1% for AVol model and 64.5% for TVol model) was significantly higher than that of the traditional 2D model (19.4%) 68 …”
Section: How To Establish a Chinese Fetal Growth Standardmentioning
confidence: 83%
See 2 more Smart Citations
“…A multicenter study indicated that the inclusion of automated FLV measurements improved the proportion of correctly classified birthweight ± 10% in >80% of cases than 73.8% for the INTERGROWTH-21 st model 64 . For Chinese fetuses in the third trimester, particularly newborns weighing <3500 g, the percentage of estimated error ≤ 5% using the automated limb volume estimation software (58.1% for AVol model and 64.5% for TVol model) was significantly higher than that of the traditional 2D model (19.4%) 68 …”
Section: How To Establish a Chinese Fetal Growth Standardmentioning
confidence: 83%
“…introduced the concept of FLV, which provided a new way of evaluating soft tissue for weight prediction 65 . Since then, numerous studies have shown that a combination of 2D and 3D parameters can improve the precision of EFW 64,66–68 . During the second and third trimesters of pregnancy, incorporation of 3D data, such as fractional arm volume (AVol) or fractional thigh volume (TVol), into estimation models reduced the random error to 6.6% 66 .…”
Section: How To Establish a Chinese Fetal Growth Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates the high accuracy of fetal weight estimation by ultrasound, and this finding is consistent with the results of previous studies. [ 14 15 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…4D ultrasound), generating continuous 3D volume data sets and providing functional and dynamic data in three dimensions (Hildebrandt et al., 2009 ; Mattoon et al., 2002 ). Both 3D and 4D volume ultrasonography are well established in human obstetrics and gynaecology (Merz & Welter, 2005 ) and have been reported to offer the advantage to allow the analysis of a number of clinical conditions including congenital disorders or foetal deformities even allowing the demonstration of subtle foetal defects, foetal gender determination, gestational age and birth weight assessment (Kotoyori et al., 2012 ; Merz & Pashaj, 2017 ; Wu et al., 2021 ; Youssef et al., 2011 ). Their establishment in human medicine is also based on an important emotional aspect for the parents, allowing them to see a concrete 3D reconstruction of their babies, helping them to understand and accept possible existing malformations, or to reassure them of the absence of foetal abnormalities (Merz & Pashaj, 2017 ; Merz & Welter, 2005 ).…”
Section: Introductionmentioning
confidence: 99%